Effect of Recruitment and Training on Employee Turnover Intention at Bfi Finance Serpong - Dewi Sartika (Peneliti.net, 2022)
The purpose of the research that the author did was to determine the effect of recruitment on Turnover Intention, the effect of training on Turnover Intention. And to determine the effect of recruitment and training together on Turnover Intention at PT BFI Finance Serpong. The population and sample in this study were employees at PT BFI Finance Serpong, totaling 112 samples using the saturated sample technique.The research method used by the author is a quantitative descriptive method,methoddata collection by distributing questionnaires which are then processed using regression analysis.The test used to test the research instrument in the form of validity and reliability tests. classic assumption test, namely: normality test, multicollinearity test, and autocorrelation test. Hypothesis test consists of: correlation test, determination test Simple linear regression test, multiple linear regression test, t test (partial) and F test (simultaneous)with the help of SPSS 24 Software for Windows.Based on the results of the research on the descriptive test, it is known that the variablerecruitmentthe number of statements answered with the word agreeas big as53.3% or with the agree criteria, the training variable with agreeing 54.7% or agreeing criteria, and those who answered agreeing on the Turnover Intention variable with 54.3% agreeing or agreeing with the statement. Analysis resultThere is a positive and significant influence between recruitment and training on Turnover Intention at PT BFI Finance Serpong. This can be seen from the multiple linear regression value Y = 13,465 + 0,569 X1 + 0,447 X2,constant value of13,465shows that if Recruitment (X1) and Training (X2) is worth 0, then the Turnover Intention value is13,465.The correlation coefficient value is 0.861,the coefficient of determination of the recruitment and training variables contributed to the effect of74.2%, the effect of recruitment and training on Turnover Intention is significant because it has a value ofFcount 11.065 > Ftable 3.08 and significant value 0.000 <0.05.